Better living through chems: Fallout’s post-apocalyptic pharmacy - Wallin, Jason James (Loading)

(untitled) (Canadian Game Studies Association, 2019)
Contemporary climate change research today speculates that life as we know it is at an end (Scranton, 2015). As planetary conditions optimal to the survival of the human species are undergoing profound transformation, the question of what future awaits the human species has become both prominent and pervasive. Extending into the speculative art of video games, this post-apocalyptic mis-en-scene today constitutes something of a familiar reference point for gamers, who might find in such popular games as Left 4 Dead (2008) and Gears of War (2006) a particular speculation on survival where life as we know it encounters the destructive forces of nuclear devastation, epidemic, invasion, or any one of a myriad catastrophic scenarios now cliché in the medium. Yet, the ways that video games think survival nevertheless constitutes a speculative fulcrum on which is dramatized both “world without-us”, or rather, an impersonal hostile world unremitting to the desires of ‘man’, and the human that might survive it (Thacker, 2011). Significant amongst such speculative games are the massive post-apocalyptic worlds of Fallout 3, Fallout: New Vegas, and Fallout 4, each of which evokes the question of how we might survive after nuclear catastrophe and its transformation of the planet into a foreboding ecology populated by mutated animals, radioactive dead-zones, loosely organized bandit hordes, and nomads foraging the resource scarce post-apocalyptic future.